Book Reviews. Issue 3 (1st December 2022) - Wood, Lesley; Barnett, Ronald; Welch, Penny
Abstract : Budd L. Hall and Rajesh Tandon (2021), Socially Responsible Higher Education: International Perspectives on Knowledge Democracy . Rotterdam, NL: Brill, 303pp., ISBN: 978-90-04-45907-6 Anke Schwittay (2021), Creative Universities: Reimagining Education for Global Challenges and Alternative Futures . Bristol: Bristol University Press, 200pp., ISBN: 978-1529213652 Catherine Bovill (2020) Co-creating Learning and Teaching: Towards Relational Pedagogy in Higher Education . St. Albans: Critical Publishing, 96pp., ISBN: 9781913063818